Impact of heavy metals on Ciconia boyciana feathers and Larus saundersi egg shells in the Yellow River delta estuary. Issue 65 (27th October 2020) - Yang, Yuewei; Li, Jing; Zhang, Fengjiao; Sun, Fengfei; Chen, Junfeng; Tang, Meizhen
Abstract : In this study, the Ciconia boyciana and Larus saundersi, typical wetland birds in the Yellow River estuary, were selected as research objects. Abstract : In this study, the Ciconia boyciana and Larus saundersi, typical wetland birds in the Yellow River estuary, were selected as research objects. The feathers and egg shells of Ciconia boyciana and Larus saundersi were collected to determine the contents of heavy metals Cd, Cr, Cu, Zn, Mn, Ni and Pb in the samples. Correlation analysis (CA), principal component analysis (PCA), principal factor analysis (PFA) and potential ecological risk index (RI) were used to analyse and treat the measured heavy metal content data to determine the heavy metal pollution status, source and potential ecological risk in the Yellow River estuary. The results of CA, PCA and PFA showed that the content of Cd in the Yellow River estuary was much higher than the background value and its pollution was the most serious. Cr pollution was second and Mn pollution was the lowest. Heavy metal pollution mainly came from human activities such as oil exploitation, industrial production, use of pesticides and fertilizers, and the pollution caused by natural sources was relatively low. Based on the RI value of heavy metals in the study area, heavy metal Cd had an extremely high ecological risk status, and other heavy metals were all low. The results of this study can provide some reference and theoretical support for bird protection, heavy metal pollution control and ecological restoration in the Yellow River delta.